Morphological characteristics of the superior cerebellar artery - Ace, Dodevski; Lazarova, Dobrila; Zhivadinovikj Bogdanovska, Julija; Lazareska, Menka; Stojovska Jovanovska, Elizabeta (Macedonian Academy of Sciences and Arts, 2015)
With the introduction of new techniques in diagnostic and interventional radiology and progress in micro neurosurgery, accurate knowledge of the brain blood vessels is essential for daily clinical work. The aim of this study was to describe the morphological characteristics of the superior cerebellar artery and to emphasize their clinical significance. In this study we examined radiographs of 109 patients who had CT angiography at the University Clinic for Radiology in Skopje, R. Macedonia. This study included 49 females and 60 males, ranging in age from 27 to 83 years; mean age 57.4 ± 11.8 years. In 105 patients SCA arose from the basilar artery on both sides as a single vessel. In two patients SCA arose as a duplicate trunk from the basilar artery. We found unilateral duplication on the right SCA in one patient, and bilateral duplication in one patient. In two patients was noticed origin of the SCA from PCA as a single trunk from adult type of the PCA. Through knowledge of the anatomy and variations of SCA is important for clinicians as well as basic scientists who deal with problems related to intracranial vasculature in daily basis for save performance of diagnostic and interventional procedures.
Keywords: superior cerebellar artery; anatomy; variations; basilar artery